2011
DOI: 10.1007/s10904-011-9631-2
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Spectral, Morphology, Thermal Degradation Kinetics and Antibacterial Studies of Terpolymer Metal Complexes

Abstract: Terpolymer metal complexes involving transition metal ions such as Cu(II), Mn(II) and Zn(II) were prepared using a terpolymer ligand derived from anthranilic acid-phenyl hydrazine-formaldehyde (APHF). The terpolymer ligand and its metal complexes were intended to spectral characterizations viz. FTIR, electronic, ESR, 1 H NMR and 13 C NMR to elucidate the structural confirmations. The number, weight, and size average molecular weights of the terpolymer ligand were determined by gel permeation chromatography (GP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 34 publications
(28 reference statements)
0
10
0
Order By: Relevance
“…The g values can also be used to calculate the magnetic field ( G ) value from the following equation: From the above equation, if G is less than 4.0, the ligand is regarded as a strong field ligand. The G value for AAPF Cu is 1.177 which clearly establishes that the AAPF Cu complex forms with a strong field ligand …”
Section: Resultsmentioning
confidence: 73%
See 1 more Smart Citation
“…The g values can also be used to calculate the magnetic field ( G ) value from the following equation: From the above equation, if G is less than 4.0, the ligand is regarded as a strong field ligand. The G value for AAPF Cu is 1.177 which clearly establishes that the AAPF Cu complex forms with a strong field ligand …”
Section: Resultsmentioning
confidence: 73%
“…Kinetic and thermodynamic parameters were calculated and the thermal degradation mechanism was also proposed. The antibacterial activity was tested against certain pathogenic bacteria and the results proved that the ligand and its metal complexes had good activity against the growth of those bacterial strains …”
Section: Introductionmentioning
confidence: 99%
“…The developed chitosan‐copolymer blend membranes were screened for antibacterial activity by disc diffusion technique according to earlier literature . The bacterial strains used for the analysis are Escherichia coli, Staphylococcus aureus (ATCC 25923) and Salmonella typhimurium (ATCC 23564).…”
Section: Methodsmentioning
confidence: 99%
“…The thermal stability of the synthesized compounds was determined and the results proved that all the compounds were thermally highly stable. The compounds were also screened for antibacterial activity and the results confirmed that all the metal complexes were more potent antibacterial agents than their respective ligands, which is quite naturally due to the incorporation of metal ions into the polymeric backbone …”
Section: Introductionmentioning
confidence: 91%